A new carbon nanoparticle-polymer composite for cell imprint lithography - Vigneswaran, Narayanamurthy (2017)
Morphological features of cells play a vital role in cell research, drug delivery, diagnostic, therapeutic and many other applications. Bioimprint is a soft lithography technique used to obtain the imprint replica of cell morphology. Herein report a new process approach of morphology feature extraction from the imprint replica technique. Morphological features like shape and size of cell, shape and size of nucleus, pores in the cell membrane can be imaged comparatively and the same can be detected. This technique helps to investigate the shape of grooves, pores, blebs or microvillus on the cellular surface and helps in better diagnosis and analysis at single cell level. However conventional method involving fixation, sectioning and viewing under scanning electron microscope (SEM) or transmission electron microscope (TEM) can provide cell’s inside anatomy details, although the process introduces variations in samples due to complex and tedious process involved. Also microfluidics-based biochip plays a vital role in single cell research applications. Handling and positioning of single cells at the microscale level is an essential need for quite various applications including genomics, proteomics, secretomics, and lysis analysis. Characterized the effect of microfluidic channel (straight channel, branched channel, and serpent channel) with a microwell array orientation for single cell trapping. Demonstrated microfluidic-based biochips capable of vertical cell trapping with a hexagonal array of microwells. Microwells were of 35 μm in diameter, a size sufficient to allow attachment of captured cells for short term study. Explained the process flow for the fabrication of the biochip. Single cell capture (SCC) capabilities of the microfluidic-biochips were found to be improving from the straight channel, branched channel, and serpent channel accordingly. Multiple cell capture (MCC) were in the order of decreasing from the straight channel, branch channel, and serpent channel. Among three designs investigated, serpent channel biochip offers high SCC with reduced MCC. Human lung cancer cells were used for characterization. The findings of this research is that developed a novel approach of carbon nanoparticle-polymer composite (CPC) for imaging technique for the cells, which can provide morphology information on single cell sub organelle scale in much detail. It is observed that 0.3 wt. % of load carbon nanoparticle (CNP) in carbon polymer mixture (CPM) were optimal for cell-imprint replica fabrication. The electrical resistance of the 3-CPC (0.3 wt. %) were reduced by 68 % when compared to N-CPC (0 wt. %). Electron microscopes were used to image the replica. Technique delivers cell image along with its complete sub cell scale level morphological details. The limitation of this technique is that, it only provides the morphology information. Thus abnormalities which do not designate on morphology cannot be diagnosed. This technique finds its application where single cells are to be analyzed and diagnosis for study based on morphology, especially for drug delivery applications and for investigations based on molecular pathways. As a future prospective, morphology features obtained through this technique can also be used to train the artificial neural network for decision making completely based on this technique.